Sajjata Sangh : a network of NGOs - Bikkina, Nalini; Sarin, Ankur (London : SAGE Publications Ltd, 2017)
Sajjata Sangh was initiated with the mission of promoting sustainable livelihood practices based on agriculture and had been encouraging its network organizations to focus on being accredited by Creditability Alliance. Sajjata Sangh advocated accreditation to ensure managerial competency, accountability and transparency in the functioning of NGOs across Gujarat. A spin-off of this initiative was the listing of some of the network NGOs of Sajjata Sangh which expressed willingness to undergo the pro.
Originally published: Bikkina, N., & Sarin, A. (2013). Sajjata Sangh: A network of NGOs. PSG0112. Ahmedabad: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sajjata Sangh; Nonprofit organizations -- India -- Gujarat; Sustainable development -- India -- Gujarat; Sustainable agriculture -- India -- Gujarat